Pengenalan Sumber Bacaan Sederhana Sebagai Sarana Peningkatan Literasi Baca Untuk Siswa SD - Ira Restu Kurnia; Septian Mukhlis; Listian Indriyani Achmad; Ismail Nurahmadi (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2024)
Reading literacy can be defined as a person's ability to understand, evaluate and use information contained in reading effectively. Reading literacy is an ability that must be familiarized from an early age. One of the factors that can improve reading literacy is the existence of simple reading resources that can be tailored to student needs. In this case, the role of parents, especially teachers, is very important to support students in reading activities. through this community service activity, the results obtained regarding the understanding of SDN 2 Bojongmenteng teachers increased. Teachers understand the types of simple reading materials that can improve students' reading literacy. From this activity, teachers are expected to be able to implement simple reading for students of SDN 2 Bojongmenteng.